Functionalized loofah sponge-based adsorbent as well as preparation method and application thereof

The loofah is modified through surface charge regulation technology, and the problems of cumbersome preparation and unfriendly environmentally friendly traditional carbon-based adsorption materials are solved, and efficient and environmentally friendly dye adsorption is achieved, which is suitable for water treatment and environmental protection.

CN119303551APending Publication Date: 2025-01-14ANHUI AGRICULTURAL UNIVERSITY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411857491.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The preparation process of traditional carbon-based adsorbent materials is cumbersome, has high energy consumption and is not environmentally sustainable, making it difficult to effectively treat dye wastewater.

Method used

Using loofah as raw material, through surface charge regulation technology, quaternary aminated loofah with positive surface charge and carboxylated loofah with negative surface charge were prepared. It uses its porous structure and rich surface groups to improve adsorption performance. .

Benefits of technology

It realizes efficient, environmentally friendly and pollution-free dye adsorption, significantly improves adsorption capacity, reduces preparation costs, and is renewable, suitable for applications in the fields of environmental protection and water treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119303551A_ABST
    Figure CN119303551A_ABST
Patent Text Reader

Abstract

The invention provides a functionalized loofah sponge-based adsorbent and a preparation method thereof, and the preparation method comprises the following steps: cutting loofah sponge, and delignifying with sodium hydroxide; preparing a CHPTAC solution to obtain a treatment solution; the delignification loofah sponge blocks are immersed in NaOH to be heated, then treatment liquid is added, and heating reaction is conducted; and cleaning. The invention also provides another functional loofah sponge-based adsorbent and a preparation method thereof, and the preparation method comprises the following steps: cutting loofah sponge, and delignifying by adopting a sodium chlorite / glacial acetic acid system; preparing TEMPO-NaBr, and adding a sodium hypochlorite solution to obtain a treatment solution; immersing delignification loofah sponge blocks into the treating fluid, and heating for reaction; and cleaning. The invention also provides application of the two adsorbents as dye adsorbents. The modified loofah sponge with two different charge surfaces is prepared by performing charge regulation and control on groups on the loofah sponge surface, the modified loofah sponge is used as a dye adsorbent, the adsorption performance is good, and the preparation process is simple, environment-friendly and pollution-free.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of biological adsorption materials, and in particular to a functionalized loofah-based adsorbent and a preparation method and application thereof. Background Art

[0002] Although wastewater treatment technology continues to advance, it still faces many challenges in terms of adsorption efficiency, cost control and environmental adaptability. In this context, adsorption is widely favored by the industry due to its simple operation and cost-effectiveness.

[0003] However, the preparation process of traditional carbon-based adsorption materials is cumbersome, energy-intensive, and not environmentally sustainable, which limits their wide application. In order to explore a more efficient solution, the present invention uses the agricultural and sideline product loofah as a raw material, and through the innovative use of surface charge regulation technology, the loofah surface has a significant positive charge or negative charge, which significantly improves the adsorption performance of loofah to ionic dyes. At the same time, loofah, as a natural porous biomass material, also shows excellent adsorption capacity after modification, and has a stronger processing capacity for dye wastewater. In addition, loofah raw materials are abundant and renewable, and have excellent environmental compatibility. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a functionalized loofah-based adsorbent with good adsorption performance, simple preparation process, environmental protection and no pollution, and a preparation method and application thereof.

[0005] The present invention adopts the following technical solutions to solve the above technical problems: A method for preparing a functionalized loofah-based adsorbent, which is used to prepare a quaternary ammonium loofah with a positive surface charge, comprises the following steps: (1) cutting the loofah and performing delignification treatment with sodium hydroxide to obtain a delignified loofah block; (2) preparing a CHPTAC solution (3-chloro-2-hydroxypropyltrimethylammonium chloride) to obtain a treatment solution; (3) Immerse the delignified loofah block in a NaOH solution and heat it in a water bath at 50-80°C for 0.5-1h, then add the treatment solution and heat it in a water bath at 50-80°C for 2-5h; (4) Take out the loofah pieces and wash them.

[0006] As one of the preferred embodiments of the present invention, in step (1), the specific process of delignification treatment is as follows: ① Prepare sodium hydroxide solution with a mass concentration of 9-11%; ② Soak the loofah pieces in sodium hydroxide solution and heat in a water bath at 80-100℃ for 1-5h; ③Take out the loofah pieces and wash them with ethanol and water.

[0007] As one of the preferred embodiments of the present invention, in step (2), the mass concentration of the NaOH solution is 8-10%, and the mass concentration of the CHPTAC solution is 1-3%.

[0008] As one of the preferred embodiments of the present invention, in step (4), the washing sequence is ethanol and pure water.

[0009] A functionalized loofah-based adsorbent (quaternary ammonium loofah with positive surface charge) is prepared by adopting the preparation method.

[0010] At the same time, the present invention also provides another method for preparing a functionalized loofah-based adsorbent, which is used to prepare a carboxylated loofah with a negative surface charge, and the steps are as follows: (1) cutting the loofah and performing delignification treatment using a sodium chlorite / glacial acetic acid system to obtain a delignified loofah block; (2) preparing a TEMPO-NaBr system and adding a sodium hypochlorite solution to obtain a treated solution; (3) Immerse the delignified loofah pieces in the treatment solution and heat them in a water bath at 70-100°C for 2-5 hours; (4) Take out the loofah pieces and wash them.

[0011] As one of the preferred embodiments of the present invention, in step (1), the specific process of delignification treatment is as follows: ① Prepare a sodium chlorite solution with a mass concentration of 1.5-2.5%, and add 6-8 drops of glacial acetic acid solution into it; ② Soak the loofah pieces in sodium chlorite solution and heat in a water bath at 80-100℃ for 1-5 hours; ③Take out the loofah pieces and wash them with ethanol and water.

[0012] As one of the preferred embodiments of the present invention, in the step (2), in the TEMPO-NaBr system, the mass ratio of TEMPO (2,2,6,6-tetramethylpiperidinyl oxide) to NaBr is 4:25, and the pH is 9-11.

[0013] As one of the preferred embodiments of the present invention, in step (2), the mass concentration of the added sodium hypochlorite solution is 9-11%.

[0014] As one of the preferred embodiments of the present invention, in step (4), washing is performed with ethanol.

[0015] A functionalized loofah-based adsorbent (carboxylated loofah with negative surface charge) is prepared by the preparation method.

[0016] At the same time, the present invention also provides the use of the above-mentioned "quaternary ammonium loofah with positive surface charge" or "carboxyl loofah with negative surface charge" as a dye adsorbent, and the dye includes but is not limited to methylene blue (MB) and Congo red (CR).

[0017] The present invention controls the charge of the groups on the surface of the loofah so that the loofah has more exposed hydroxyl groups and amino groups, thereby preparing two modified loofahs with different charge surfaces. Compared with the prior art, the advantages of the present invention are: (1) The present invention adopts a top-down strategy to directly utilize the original structure and unique biomass characteristics of widely available biomass loofah, which not only realizes the effective utilization and transformation of resources, avoids the high energy consumption and environmental damage of traditional materials, but also produces efficient, environmentally friendly and pollution-free adsorption materials through a low-energy processing process. The present invention proves that the crystallinity of the treated loofah does not decrease. The natural porous structure and rich surface groups of loofah not only ensure the efficient removal ability of various pollutants, but also maintain low cost and easy accessibility. As a renewable, degradable and environmentally friendly material, the biomass adsorbent is easy to remove after use, does not produce secondary pollution, and can be regenerated through simple treatment, which significantly improves the sustainability of resources.

[0018] (2) The present invention cleverly utilizes the porous biomass material of loofah. Its porous structure (porosity of 79-93%) is combined with its high cellulose content. This unique combination provides sufficient natural adsorption sites for loofah, which not only improves its adsorption capacity, but also enables it to effectively capture and fix a variety of pollutants and achieve efficient purification. At the same time, the high cellulose content ensures that the loofah has excellent mechanical strength and stability. Compared with traditional carbon powder materials, the loofah can maintain its structural integrity even during the adsorption process and is not easily damaged. Moreover, the two-step treatment of the present invention not only optimizes the pore structure of the loofah, but also introduces more functional groups on the surface of the loofah, such as -COOH, NH, etc. These functional groups can not only promote the attachment of methylene blue and Congo red through physical adsorption, but also further enhance the adsorption efficiency through chemical adsorption (such as π-π interaction and hydrogen bonding). The successful surface charge regulation increases the surface polarity, promotes the interaction with polar adsorbates, and thus improves the adsorption efficiency. The loofah produced by this invention has more adsorption sites and fewer impurity defects. This feature makes loofah an ideal choice for preparing high-performance, renewable adsorption materials. It not only meets the demand for efficient and environmentally friendly treatment technology, but also promotes the sustainable use of resources, showing great application potential and market value in the fields of environmental protection and water treatment.

[0019] (3) The present invention innovatively introduces selective delignified loofah, and significantly enhances its adsorption performance for anions and cations through quaternization and carboxylation modification. Among them, lignin has a strong adsorption capacity for Congo red dye, which is mainly attributed to the strong mutual attraction between the negatively charged Congo red molecules and the lignin molecules that may be positively charged. At the same time, hydrogen bonds form a stable connection between lignin and Congo red molecules, making it more difficult for Congo red molecules to detach from the lignin surface, thereby ensuring the durability and firmness of the adsorption effect. And the adsorption capacity is significantly enhanced compared to the original loofah. By completely removing the lignin from the loofah, more hydroxyl groups on the surface of the loofah are exposed, which provides sufficient conditions for carboxylation modification.

[0020] (4) The present invention modifies the loofah by quaternization and carboxylation, and precisely controls its surface charge, thereby significantly enhancing the adsorption capacity of the loofah. The maximum adsorption capacity of the prepared carboxylated loofah for MB is as high as 216.87 mg / g, and the maximum adsorption capacity of the quaternized loofah for CR is as high as 247.79 mg / g, which are 1.6 times and 1.5 times higher than those of the original loofah, respectively. The high efficiency of the treated loofah in adsorbing MB and CR is mainly attributed to the combined effect of its physical and chemical dual action mechanisms. The physical action provides a large number of adsorption sites through pore filling. The MB and CR molecules are small in size (about 1.44 nm and 1 nm), and can smoothly enter the large pores (pore size of about 4 to 10 microns) on the surface of the loofah, thereby effectively avoiding the pore repulsion effect. After being treated with sodium hydroxide solution and quaternized, the loofah effectively removes its original impurities, making its adsorption performance for Congo red dye more significant. After carboxylation, negative charges are formed on the surface of the loofah, which generates a strong electrostatic attraction with the positively charged methylene blue molecules. This electrostatic interaction, coupled with the ability of the carboxyl group to form hydrogen bonds with the methylene blue molecules, enables the modified loofah to more efficiently capture and remove methylene blue from water. Multiple mechanisms such as π-π interactions, electrostatic attraction, and hydrogen bonds promote the close binding between MB and CR molecules and the loofah. This strategy not only greatly improves the adsorption performance of the loofah, but also cleverly retains its original framework structure, enabling it to efficiently and stably separate target pollutants in complex wastewater systems and achieve effective removal of target ions.

[0021] (5) The loofah prepared by the present invention exhibits rapid adsorption ability. After being added to the MB / CR solution, LS1 / LS5 can quickly adsorb MB / CR and reach adsorption equilibrium within 60 minutes. This is because the modified loofah has rich pore structure and active sites, which enables it to quickly capture dye molecules at the initial stage of adsorption. The adsorption of MB and CR by the two loofahs is more consistent with the pseudo-second-order model, indicating that the adsorption process mainly depends on the interaction strength between the treated loofah and the dye molecules, reflecting the dominant role of the chemical adsorption mechanism and the contribution of non-covalent effects. Moreover, the loofah after surface charge regulation has a higher adsorption capacity at a lower temperature (such as 25°C), reflecting that physical adsorption is more significant at low temperatures. The adsorption behavior found by fitting is consistent with the Langmuir model, indicating that the treated loofah has uniform surface active sites, there is no interaction between the adsorbed molecular layers, and a dynamic equilibrium can be established between adsorption and desorption.

[0022] (6) The cost of using loofah as a raw material is low, mainly due to its abundant natural resources and simple processing procedures. At the same time, its recyclable characteristics further improve its economic efficiency. Compared with synthetic polymer materials, the manufacturing process of loofah is more environmentally friendly because it comes from nature and does not require complex chemical synthesis steps. By converting agricultural and sideline products into environmentally friendly adsorption substrates, this innovation not only effectively solves the problem of agricultural waste, but also greatly develops and improves the potential value of this by-product. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 1 is a microstructure diagram of the quaternary ammonium loofah with positive surface charge before and after adsorption of Congo red in Experimental Example 1 (in the figure, Figure a is the cross-sectional microstructure before adsorption of Congo red, Figure b is the longitudinal microstructure before adsorption of Congo red, Figure c is the cross-sectional microstructure after adsorption of Congo red, and Figure d is the longitudinal microstructure after adsorption of Congo red); Figure 2 : This is a microstructure diagram of the carboxylated loofah with negative surface charge in Experimental Example 1 before and after the adsorption of methylene blue (in the figure, Figure a is the cross-sectional microstructure before the adsorption of methylene blue, Figure b is the longitudinal microstructure before the adsorption of methylene blue, Figure c is the cross-sectional microstructure after the adsorption of methylene blue, and Figure d is the longitudinal microstructure after the adsorption of methylene blue); Figure 3 FTIR spectra and XRD results of the original loofah and two modified loofahs in Experimental Example 1 (in the figure, Figure a is the FTIR spectrum, and Figure b is the XRD diagram); Figure 41 is the Zeta potential diagram of the original loofah and the two modified loofahs in Experimental Example 1 (in the figure, Figure a is the Zeta potential diagram of the quaternary ammonium modified loofah, Figure b is the Zeta potential diagram of the carboxyl modified loofah, and Figure c is the Zeta potential diagram of the original loofah); Figure 5 These are the adsorption performance results of LS1 and LS5 modified loofahs on CR and MB respectively at different solution pH in Experimental Example 2; Figure 6 It is the adsorption kinetics and isotherm model results of Congo red by LS1 quaternized loofah in Experimental Example 2 (in the figure, Figure a is the adsorption kinetics model, and Figure b is the adsorption isotherm model); Figure 7 These are the adsorption kinetics and isotherm model results of methylene blue by LS5 carboxylated loofah in Experimental Example 2 (in the figure, Figure a is the adsorption kinetics model, and Figure b is the adsorption isotherm model). DETAILED DESCRIPTION

[0024] The embodiments of the present invention are described in detail below. The embodiments are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and specific operation processes are given, but the protection scope of the present invention is not limited to the following embodiments. At the same time, the raw materials, reagents, and devices used in the following embodiments, unless otherwise specified, can be obtained from conventional commercial channels, or can be obtained by existing methods; unless otherwise specified, the methods used in the embodiments of the present invention are methods mastered by those skilled in the art.

[0025] Example 1 The preparation method of the quaternized loofah LS1 with positive surface charge in this embodiment is as follows: (1) Cut the loofah to obtain loofah blocks; prepare a sodium hydroxide solution with a mass concentration of 10%; immerse the loofah blocks in the sodium hydroxide solution, and heat them in a 90°C water bath for reaction for 2 hours; take out the loofah blocks, wash them with ethanol, and then wash them with deionized water for 5 times to obtain delignified loofah blocks.

[0026] (2) Prepare a CHPTAC solution with a mass concentration of 2% to obtain a treatment solution.

[0027] (3) Immerse the delignified loofah block from step (1) in a prepared 10% NaOH solution and heat it in a 60°C water bath for 0.5 h. Then add the treatment solution from step (2) and heat it in a 60°C water bath for 2 h.

[0028] (4) Take out the loofah piece, wash it with ethanol, and then wash it with deionized water for 5 times to obtain the quaternary ammonium modified loofah LS1, which is then soaked in deionized water for standby use.

[0029] Example 2 The quaternized loofah LS2 of this embodiment has a positive surface charge, and the preparation method is as follows: (1) Cut the loofah to obtain loofah blocks; prepare a sodium hydroxide solution with a mass concentration of 9%; immerse the loofah blocks in the sodium hydroxide solution, and heat them in a water bath at 80° C. for 5 h; take out the loofah blocks, wash them with ethanol, and then wash them with deionized water for 5 times to obtain delignified loofah blocks.

[0030] (2) Prepare a CHPTAC solution with a mass concentration of 1% to obtain a treatment solution.

[0031] (3) The delignified loofah pieces prepared in step (1) were immersed in a prepared 8% NaOH solution and heated in a 50°C water bath for 1 h. The treatment solution prepared in step (2) was then added and heated in a 50°C water bath for reaction for 5 h.

[0032] (4) Take out the loofah pieces, wash them with ethanol, and then wash them with deionized water for 5 times to obtain the quaternized ammonium modified loofah LS2, which is then soaked in deionized water for later use.

[0033] Example 3 The preparation method of the quaternized loofah LS3 with positive surface charge in this embodiment is as follows: (1) Cut the loofah to obtain loofah blocks; prepare a sodium hydroxide solution with a mass concentration of 11%; immerse the loofah blocks in the sodium hydroxide solution, and heat the solution in a water bath at 100° C. for 1 h; take out the loofah blocks, wash them with ethanol, and then wash them with deionized water for 5 times to obtain delignified loofah blocks.

[0034] (2) Prepare a CHPTAC solution with a mass concentration of 3% to obtain a treatment solution.

[0035] (3) The delignified loofah pieces prepared in step (1) were immersed in a prepared 10% concentration NaOH solution and heated at 80°C for 0.6 h. The treatment solution prepared in step (2) was then added and heated in a water bath at 80°C for 3 h.

[0036] (4) Take out the loofah pieces, wash them with ethanol, and then wash them with deionized water for 5 times to obtain the quaternized ammonium modified loofah LS3, which is then soaked in deionized water for later use.

[0037] Example 4 The preparation method of the carboxylated loofah LS4 with negative surface charge in this embodiment is as follows: (1) Cut the loofah to obtain loofah blocks; prepare a sodium chlorite solution with a mass concentration of 1.5%, and add 6 drops of glacial acetic acid solution into the solution; immerse the loofah blocks in the sodium chlorite solution, and heat them in a water bath at 80°C for 5 hours; take out the loofah blocks, wash them with ethanol, and then wash them with deionized water for 5 times to obtain delignified loofah blocks.

[0038] (2) Prepare 500 ml of TEMPO-NaBr system (pH 9) containing 0.08 g of TEMPO and 0.5 g of sodium bromide; then, add 10 ml of 9% sodium hypochlorite solution to the TEMPO-NaBr system solution to obtain a treated solution.

[0039] (3) The delignified loofah block obtained in step (1) is immersed in the treatment solution of step (2) and heated in a 70° C. water bath for reaction for 5 h.

[0040] (4) Take out the loofah pieces, wash them with ethanol to obtain carboxylated loofah LS4, and soak them in deionized water for later use.

[0041] Example 5 The preparation method of the carboxylated loofah LS5 with negative surface charge in this embodiment is as follows: (1) Cut the loofah to obtain loofah blocks; prepare a sodium chlorite solution with a mass concentration of 2%, and add 7 drops of glacial acetic acid solution into the solution; immerse the loofah blocks in the sodium chlorite solution, and heat them in a 90°C water bath for reaction for 2 h; take out the loofah blocks, wash them with ethanol, and then wash them with deionized water for 5 times to obtain delignified loofah blocks.

[0042] (2) Prepare 500 ml of TEMPO-NaBr system (pH 10) containing 0.08 g of TEMPO and 0.5 g of sodium bromide; then, add 10 ml of 10% sodium hypochlorite solution to the TEMPO-NaBr system solution to obtain a treated solution.

[0043] (3) The delignified loofah block obtained in step (1) is immersed in the treatment solution of step (2) and heated in a 90° C. water bath for reaction for 3 h.

[0044] (4) Take out the loofah block, wash it with ethanol to obtain carboxylated loofah LS5, and soak it in deionized water for later use.

[0045] Example 6 The preparation method of the carboxylated loofah LS6 with negative surface charge in this embodiment is as follows: (1) Cut the loofah to obtain loofah blocks; prepare a sodium chlorite solution with a mass concentration of 2.5%, and add 8 drops of glacial acetic acid solution into the solution; immerse the loofah blocks in the sodium chlorite solution, and heat the solution in a water bath at 100°C for 1 hour; take out the loofah blocks, wash them with ethanol, and then wash them with deionized water for 5 times to obtain delignified loofah blocks.

[0046] (2) Prepare 500 ml of TEMPO-NaBr system (pH 11) containing 0.08 g of TEMPO and 0.5 g of sodium bromide; then, add 10 ml of 11% sodium hypochlorite solution to the TEMPO-NaBr system solution to obtain a treated solution.

[0047] (3) The delignified loofah block obtained in step (1) is immersed in the treatment solution of step (2) and heated in a 100° C. water bath for 2 h.

[0048] (4) Take out the loofah block, wash it with ethanol to obtain carboxylated loofah LS6, and soak it in deionized water for later use.

[0049] Comparative Example 1 The preparation method of a loofah LS1' in this comparative example is basically the same as that in Example 1, the main difference is that: in step (1), the loofah block is not subjected to delignification treatment; correspondingly, in step (3), the natural loofah block is immersed in the treatment liquid and heated for reaction.

[0050] Comparative Example 2 The preparation method of the loofah LS2' in this comparative example is basically the same as that in Example 1, except that the quaternary ammonium modification treatment in steps (2) and (3) is not performed.

[0051] Comparative Example 3 The preparation method of a loofah LS3' in this comparative example is basically the same as that in Example 1, except that: in step (1), a sodium chlorite / glacial acetic acid system is used for delignification treatment: a sodium chlorite solution with a mass concentration of 2% is prepared, and 7 drops of glacial acetic acid solution are dripped into it; the loofah block is immersed in the sodium chlorite solution, and heated in a 90°C water bath for reaction for 2 hours; the loofah block is taken out and washed with ethanol and clean water.

[0052] Comparative Example 4 The preparation method of the loofah LS4' in this comparative example is basically the same as that in Example 5, except that the carboxylation improvement treatment in steps (2) and (3) is not performed.

[0053] Comparative Example 5 The preparation method of the loofah sponge LS5' in this comparative example is basically the same as that in Example 5, the main difference is that in step (1), glacial acetic acid is not added during delignification.

[0054] Experimental Example 1 This experimental example is used to test and analyze the structural characteristics of two modified loofah materials of the present invention.

[0055] 1. Dye adsorption experiments were performed on the quaternized loofah with a positive surface charge (taking LS1 in Example 1 as an example) and the carboxylated loofah with a negative surface charge (taking LS5 in Example 5 as an example), and the microstructural changes of the two before and after adsorption were observed.

[0056] Figure 1 The microstructure of the quaternized loofah with positive surface charge before and after adsorption of Congo red (CR), among which, a and b are the microstructures before adsorption of Congo red, and c and d are the microstructures after adsorption of Congo red. It can be clearly seen from the figure that after the quaternization treatment of the loofah, the three-dimensional porous structure and honeycomb vascular tube of the loofah remain intact, and the fiber surface shrinks. The increase in roughness is conducive to increasing the contact area between the loofah and the dye molecules and promoting adsorption; after adsorption, many Congo red dye molecules are attached to the loofah fibers, and these dye molecules are mainly adsorbed on the surface through electrostatic interaction and hydrogen bonds, indicating that the loofah adjusted to a positive charge has a strong adsorption effect on the Congo red dye molecules.

[0057] Figure 2 The microstructure of the carboxylated loofah with negative surface charge before and after the adsorption of methylene blue (MB), where a and b are the microstructures before the adsorption of methylene blue, and c and d are the microstructures after the adsorption of methylene blue. It can be clearly seen from the figure that the surface morphology of the loofah carboxylated by TEMPO is looser, and a large number of cellulose fibers have been exposed on the wrinkled surface, but the overall morphology is still maintained; by observing the image after adsorption, it can be seen that the methylene blue dye molecules are also dispersed in large quantities on the surface of the loofah, and the presence of dye molecules is also found in the pores of the loofah, indicating that pore filling also plays an important role in the adsorption process.

[0058] 2. FTIR spectrum analysis and XRD analysis were performed on the original loofah, the quaternary ammonium loofah with positive surface charge (taking LS1 in Example 1 as an example), and the carboxylated loofah with negative surface charge (taking LS5 in Example 5 as an example).

[0059] Figure 3 a is the FTIR spectra of the original loofah and two modified loofahs (quaternary ammonium loofah with positive surface charge and carboxyl loofah with negative surface charge). It can be seen from the figure that the three types of loofahs have a 1057~1070cm -1 1730~1460cm -1 、2920cm -1、3430cm -1 There is an obvious absorption peak at 1057cm -1 3430cm -1 The absorption band at 1730~1470cm is caused by the stretching vibration of –OH, which mainly comes from cellulose, hemicellulose, polysaccharides and monosaccharides; -1 The absorption band at 2901~2910cm is the characteristic absorption peak of lignin; -1 The absorption peak at 1630~1470cm is the characteristic band of CH and CH2 in cellulose and hemicellulose, which is caused by CH stretching vibration. -1 The disappearance of the absorption peak at 1057 cm indicates that the conjugated carbonyl groups in lignin are partially removed. -1 3430cm -1 The absorption peaks at 1617 cm-1 and 1617 cm-2 of the quaternary ammonium modified loofah appeared. -1 ) stretching vibration peak, and NH (3416cm -1 、1637cm -1 and 1058.91cm -1 ) has a significant increase in peak intensity.

[0060] Figure 3 b is the XRD diagram of the original loofah and two modified loofahs (quaternary ammonium loofah with positive surface charge and carboxylated loofah with negative surface charge). It can be seen from the figure that compared with the natural cellulose I-shaped structure of the original loofah, the characteristic peak of cellulose in the carboxylated loofah has not changed, indicating that the cellulose structure has not changed. The characteristic peak is sharper after treatment, which indicates that non-crystalline structures such as lignin, hemicellulose and pectin are selectively removed, and the main retained cellulose shows stronger crystallinity. The quaternary ammonium treated loofah shows a transition from cellulose I-shaped structure to cellulose II-shaped structure. This is because the loofah has been treated with alkali. During the treatment, hydrated sodium ions will enter the crystallization area, thereby swelling the cellulose. After treatment and washing, sodium ions flow out of the loofah, causing the loofah to form a cellulose I-shaped crystalline structure during the recrystallization process.

[0061] Meanwhile, the original loofah and the two modified loofahs had broad diffractions at 10-18° and 20-25°, indicating an amorphous structure. The diffraction peaks of the two modified loofahs at 20-25° became sharper and stronger than those of the untreated loofah fibers, indicating that the crystallinity was enhanced due to the removal of non-crystalline materials such as lignin, hemicellulose, and pectin.

[0062] 3. Zeta potential analysis was performed on the original loofah, the quaternized loofah with positive surface charge (taking LS1 in Example 1 as an example), and the carboxylated loofah with negative surface charge (taking LS5 in Example 5 as an example).

[0063] Figure 4 a is the Zeta potential diagram of the quaternary ammonium modified loofah, which shows the success of the regulation of the positive charge on the surface of the quaternary ammonium modified loofah. Compared with the original loofah ( Figure 4 c) The degree of positive charge increases by nearly 25, which can better adsorb the negatively charged dye molecule CR.

[0064] Figure 4 b is the Zeta potential diagram of carboxyl modified loofah, which shows the successful regulation of negative charge on the surface of carboxyl modified loofah. Compared with the original loofah ( Figure 4 c) The degree of negative charge increased by nearly 7, which can better adsorb the positively charged dye molecule MB.

[0065] Experimental Example 2 This experimental example is used to test and analyze the performance of two modified loofah materials of the present invention.

[0066] 1. The equilibrium adsorption capacity of the modified loofah prepared in Example 1, Example 5, Comparative Example 1, Comparative Example 2, and Comparative Example 4 was tested respectively. When testing the equilibrium adsorption capacity, the temperature was set to 25°C, 1 g of the modified loofah was added, and it was placed in a Congo red solution (CR) and a methylene blue (MB) solution with an initial concentration of 500 mg / L, respectively. The test results are shown in Table 1.

[0067] Table 1 Equilibrium adsorption test results

[0068] Table 2 shows the adsorption capacity of CR and MB by differently treated loofahs. From the data in the table, it can be concluded that the adsorption capacity of the loofah after the first treatment (delignification treatment) is enhanced compared with the untreated original loofah, and the adsorption capacity of the loofah after the second treatment (quaternary ammonium modification treatment / carboxylation modification treatment) is significantly enhanced. From the table, the adsorption capacity of the loofah after the quaternary ammonium treatment is slightly worse than that of the original loofah, because the surface of the loofah after the treatment is positively charged, and the methylene blue dye molecules are electrostatically repelled, but its ability to adsorb Congo red dye is significantly enhanced. The adsorption capacity of the loofah after the carboxylation treatment is slightly worse than that of the original loofah, because the surface of the loofah after the treatment is negatively charged, and the Congo red dye molecules are electrostatically repelled, but its ability to adsorb methylene blue dye is significantly enhanced. The above illustrates the success of the surface charge regulation of the present invention.

[0069] 2. Add 1g LS1 (quaternized loofah in Example 1) and 1g LS5 (carboxylated loofah in Example 5) to 50ml Congo red solution (CR) and 50ml methylene blue (MB) solution respectively. The initial concentrations of Congo red solution and methylene blue solution are both 500mg / L. Set the pH value to 3, 5, 7, 9, 11. After adsorption equilibrium is reached, take out the solution for testing. The test results are as follows: Figure 5 shown.

[0070] Figure 5 The adsorption performance of LS1 and LS5 for CR and MB at different solution pH (3-11) was shown. The results showed that the adsorption amount of both increased with the increase of pH value. The adsorption capacity of LS1 and LS5 for CR and MB was affected by the solution pH. When the pH value was 6-7, the adsorption amount of LS1 and LS5 began to decrease, but the decreasing trend of the adsorption capacity of LS5 was not as large as that of LS1. The possible reasons are as follows: (1) The surface charge morphology of loofah will change with the change of pH value; (2) The decrease in the adsorption amount of the two loofahs under alkalinity is due to the destruction of their pore structure under alkaline conditions, and the presence of a large number of anions in the solution will affect the adsorption of the two loofahs to the two dyes, making it difficult for the dyes to diffuse to the loofah surface; (3) The small change in the adsorption amount of LS5 under higher alkalinity is due to the fact that carboxylation makes the loofah surface more negatively charged, which attracts more cationic MB through electrostatics; for the adsorption of MB by carboxylated loofah, under alkaline conditions, the loofah surface will have more negative charges (and ze The results of ta potential are consistent), and more positively charged cationic dye methylene blue is adsorbed through electrostatic interaction; under acidic conditions, the negative charge on the surface of the loofah will decrease, which may be due to the increase of hydrogen ions in the solution, some of which are combined with the charge on the surface of the loofah, resulting in the lack of corresponding binding sites for the dye molecules, thus showing a decrease in adsorption performance; for the adsorption of CR by quaternized loofah, under alkaline conditions, there are a large number of hydroxide ions in the solution, which are combined with the positively charged loofah, resulting in fewer binding sites with the Congo red dye molecules, so the adsorption performance is poorer than neutral; under acidic conditions, due to the increase of hydrogen ions in the solution, some are combined with the negatively charged anionic dye Congo red, resulting in fewer dye molecules combining with the quaternized loofah, resulting in a decrease in adsorption. It is obvious that alkaline conditions are higher than acidic conditions, but both acid and alkali will affect the structure of the fiber, so the chart shows a parabolic trend.

[0071] 3. At 25°C, 1 g of LS1 (quaternized loofah in Example 1) was added to a solution with an initial Congo red (CR) concentration of 50-1000 mg / L. After adsorption equilibrium, the solution was taken out and the MB concentration was measured by UV-visible spectrophotometer at λ = 664.4 nm. The results are shown in Figure 6 , as shown in Table 2.

[0072] Table 2 R² values ​​corresponding to the adsorption kinetics and isotherm data of the present invention

[0073] from Figure 6 b shows that with the increase of CR equilibrium concentration, the equilibrium adsorption of LS1 on CR first increases significantly, then increases slightly, and finally reaches stability. The maximum adsorption of LS1 on CR is 181.4 mg / g. The equilibrium adsorption of CR on LS1 increases rapidly with the increase of initial concentration until it stabilizes. And combined with Figure 6 a It can be seen that the upward trend of adsorption conforms to the quasi-second-order kinetic model, indicating that the adsorption process is mainly chemical adsorption, which also reflects our success in regulating the positive charge on the loofah surface.

[0074] 4. At 25°C, 1 g of LS5 (carboxylated loofah of Example 5) was added to a solution with an initial methylene blue (MB) concentration of 50-1000 mg / L. After adsorption equilibrium, the solution was taken out and the MB concentration was measured by UV-Vis spectrophotometer at λ = 550.4 nm. The measurement results are shown in Figure 7 , as shown in Table 2.

[0075] from Figure 7 b shows that with the increase of MB equilibrium concentration, the equilibrium adsorption of MB on LS5 first increases significantly, then increases slightly, and finally reaches stability. The maximum adsorption of MB on LS5 is 208.6 mg / g. The equilibrium adsorption of MB on LS5 increases rapidly with the increase of initial concentration until it stabilizes. And combined with Figure 7 a It can be seen that the upward trend of adsorption conforms to the quasi-second-order kinetic model, indicating that the adsorption process is mainly chemical adsorption, which also reflects our success in regulating the negative charge on the loofah surface.

[0076] V. In the adsorption kinetics, 0.05 g of LS1 and LS5 were added to 25 mL of MB and CR solutions with an initial concentration of 500 mg / L at 25 °C, respectively. The solutions were taken out from the container at different time intervals (1, 2, 4, 6, 8, 10, 20, 30, 60, 120, 180, 300 min), and the concentrations of MB and CR were measured by UV-Vis spectrophotometer at λ = 664.4 nm and λ = 550.4 nm. The results are shown in Table 3.

[0077] Table 3 Adsorption data of LS1 and LS5 at different time intervals

[0078] Table 3 shows the adsorption capacity of LS1 and LS5 at different times. Figure 6 ,7 From the adsorption kinetics results, it can be seen that the adsorption capacity of LS1 and LS5 increases rapidly within 30 minutes. As the adsorption process proceeds, the adsorption rate gradually decreases and reaches the final adsorption equilibrium state. Both figures are consistent with the Langmuir isotherm, indicating that the adsorption is monolayer and the loofah is treated evenly, indicating that the treated loofah can uniformly adsorb dye molecules. It can also be seen that the adsorption process can be divided into three stages: (1) rapid adsorption stage, representing the diffusion adsorption of CR and MB on the outer surface of LS1 and LS5; (2) slow adsorption stage, CR and MB gradually diffuse into the internal pores of LS1 and LS5, and the adsorption amount slowly increases; (3) equilibrium stage, as the number of CR and MB molecules on LS1 and LS5 continues to increase, the available adsorption sites decrease, and finally reach equilibrium.

[0079] 6. The equilibrium adsorption capacity of the modified loofah prepared in Example 1, Comparative Example 3, Example 5, and Comparative Example 5 was tested respectively. When testing the equilibrium adsorption capacity, the temperature was set to 25°C, 1 g of modified loofah was added, and it was placed in a Congo red solution (CR) and a methylene blue (MB) solution with an initial concentration of 500 mg / L, respectively. The test results are shown in Table 4.

[0080] Table 4 Adsorption capacity of the same modified loofah under different delignification methods (mg / g)

[0081] Table 4 shows the adsorption amount of the same modified loofah under different delignification methods. The data show that for quaternized loofah with positive surface charge and carboxylated loofah with negative surface charge, they correspond to specific delignification treatment methods respectively. The best adsorption effect can only be achieved under specific loofah delignification treatment methods.

[0082] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a functionalized loofah-based adsorbent, characterized in that: For preparing quaternized loofah with positive surface charge, the steps are as follows: (1) cutting the loofah and performing delignification treatment with sodium hydroxide to obtain a delignified loofah block; (2) preparing a 3-chloro-2-hydroxypropyltrimethylammonium chloride (CHPTAC) solution to obtain a treatment solution; (3) Immerse the delignified loofah block in a NaOH solution and heat it in a water bath at 50-80°C for 0.5-1h, then add the treatment solution and heat it in a water bath at 50-80°C for 2-5h; (4) Take out the loofah pieces and wash them.

2. The method for preparing a functionalized loofah-based adsorbent according to claim 1, wherein In the step (1), the specific process of delignification treatment is as follows: ① Prepare sodium hydroxide solution with a mass concentration of 9-11%; ② Soak the loofah pieces in sodium hydroxide solution and heat in a water bath at 80-100℃ for 1-5h; ③Take out the loofah pieces and wash them with ethanol and water.

3. The method for preparing a functionalized loofah-based adsorbent according to claim 1, wherein In the step (2), the mass concentration of the NaOH solution is 8-10%, and the mass concentration of the CHPTAC solution is 1-3%.

4. A functionalized loofah-based adsorbent, characterized in that: The method is prepared by any one of claims 1 to 3.

5. A method for preparing a functionalized loofah-based adsorbent, characterized in that: The steps for preparing carboxylated loofah with negative surface charge are as follows: (1) cutting the loofah and performing delignification treatment using a sodium chlorite / glacial acetic acid system to obtain a delignified loofah block; (2) preparing a TEMPO-NaBr system and adding a sodium hypochlorite solution to obtain a treated solution; (3) Immerse the delignified loofah pieces in the treatment solution and heat them in a water bath at 70-100°C for 2-5 hours; (4) Take out the loofah pieces and wash them.

6. The method for preparing a functionalized loofah-based adsorbent according to claim 5, wherein: In the step (1), the specific process of delignification treatment is as follows: ① Prepare a sodium chlorite solution with a mass concentration of 1.5-2.5%, and add 6-8 drops of glacial acetic acid solution into it; ② Soak the loofah pieces in sodium chlorite solution and heat in a water bath at 80-100℃ for 1-5 hours; ③Take out the loofah pieces and wash them with ethanol and water.

7. The method for preparing a functionalized loofah-based adsorbent according to claim 5, wherein: In the step (2), in the TEMPO-NaBr system, the mass ratio of TEMPO to NaBr is 4:25, and the pH is 9-11.

8. The method for preparing a functionalized loofah-based adsorbent according to claim 5, wherein: In the step (2), the mass concentration of the added sodium hypochlorite solution is 9-11%.

9. A functionalized loofah-based adsorbent, characterized in that: The method is prepared by any one of claims 5 to 8.

10. Use of the functionalized loofah-based adsorbent according to claim 4 or claim 9 as a dye adsorbent.

Citation Information

Patent Citations

  • Preparation method of wood film for adsorbing copper ions

    CN114870809A